Mae Rita Eisiau Robot - Zepf, Máire,Ando. (Graffeg Limited, 2021)
Rita's bedroom is untidy and she needs to tidy up. She would like a robot to do the work for her, but after thinking further about the mess that a super-orderly robot could create, especially at mealtimes and at Christmas, Rita decides that she is the best person to tidy her room after all. A Welsh adaptation by Anwen Pierce of Rita Wants a.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books